2020
DOI: 10.1103/physrevc.102.014311
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of enhanced octupole correlations at high spin in Nd136

Abstract: Experimental signatures of moderately enhanced octupole correlations at high spin in 136 Nd are indicated for the first time. The extracted dipole moments of two negative-parity bands are only two times smaller than those of the lanthanide nuclei with N ≈ 90 which present well-established octupole correlations. Calculations using the cranked quasiparticle random phase approximation and a model of quadrupole-octupole rotations with octupole vibrations reveal the structure of the bands and the enhanced octupole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The measured values for Ba nuclei are smaller than those in the Xe nuclei, have values similar to those of the negative-parity bands in other neighboring nuclei (see, e.g., Ref. [32]), and exhibit a slight decrease with decreasing neutron number. This is surprising, because intuitively one would expect an increase of the octupole correlations when the neutron number decreases towards the N = 56 magic number for octupole correlations.…”
Section: Possible Octupole Correlationssupporting
confidence: 70%
See 1 more Smart Citation
“…The measured values for Ba nuclei are smaller than those in the Xe nuclei, have values similar to those of the negative-parity bands in other neighboring nuclei (see, e.g., Ref. [32]), and exhibit a slight decrease with decreasing neutron number. This is surprising, because intuitively one would expect an increase of the octupole correlations when the neutron number decreases towards the N = 56 magic number for octupole correlations.…”
Section: Possible Octupole Correlationssupporting
confidence: 70%
“…The calculated octupole softness in the β 2 -β 3 plane and the high B(E 1)/B(E 2) values can be induced by the used density functional, but can also correspond to higher-lying negative-parity bands, which are yet unobserved experimentally. The 112-122 Ba and [110][111][112][113][114][115][116][117][118][119][120] Xe spectra can also be checked for octupole collectivity by the collective quadrupole-octupole rotation model (QORM) [34], as recently done for 136 Nd [32], in which enhanced octupole correlations were observed at high spin. The energy spectra are well reproduced [35], which suggests the possible existence of octupole collectivity.…”
Section: Possible Octupole Correlationsmentioning
confidence: 99%
“…(For details on the model formalism and its application see [4].) Recently the model was applied to probe the octupole collectivity in light 130−136 Nd [7] showing a capability to indicate enhanced octupole collectivity with signs of a stable QO mode in 136 Nd [8] and softer QO degrees of freedom in the remaining isotopes. It was shown that the model gradually reaches the limiting case of a transition between rigid and soft QO modes with the latter being described by another version called coherent quadrupoleoctupole model (CQOM) [9,10].…”
Section: Qorm and Alternating-parity Bands Structurementioning
confidence: 99%
“…The parameters of the fits are not given for simplicity and are available from the author upon request. Here we can only say that the obtained values are in the ranges typical for the other applications of the model [4,[6][7][8].…”
Section: Alternating-parity Bands In 118-124 Bamentioning
confidence: 99%
“…The band structure of 136 Nd is very rich, exhibiting multiple chiral bands, octupole bands, highly deformed bands, as well as oblate bands, see Refs. [33][34][35][36][37][38][39][40][41][42][43][44]. Of particular interest here are the even-and odd-spin two-quasiparticle bands with the π h 2 11/2 configuration which have been recently investigated in detail with the triaxial projected shell model, proposing their interpretation in terms of transverse wobbling motion [44].…”
Section: Introductionmentioning
confidence: 99%